Genetic alterations in benign, preneoplastic and malignant breast lesions - Mehmet Esref Kabalar; Ali Karaman; Belkis Aylu; Sevilay Akalp Özmen; Ilknur Erdem (Wolters Kluwer Medknow Publications, 2012)
Context: The c-erbB-2 proto-oncogene is a member of the epidermal growth factor receptor family and has been associated with a more aggressive breast tumor biology and resistance to some types of treatments. Aims: The aim is to investigate the correlation among bcl-2 and c-erbB-2 and the micronucleus (MN) formation in patients with early breast cancer (BC). Materials and Methods: This study was conducted between May 2010 and December 2011. We analyzed the MN frequencies in 15 patients with invasive breast carcinoma (IBC), 13 patients with intraductal proliferative lesion (IDPL) and 12 benign breast lesion (BBL). The sample consisted of 40 formalin-fixed, paraffin-embedded blocks of benign and malignant breast tissue. The specimens were evaluated for bcl-2 or c-erbB-2 immunoreactivity was semi-quantitatively evaluated in at least 1000 cells examined under the microscope at 40Χ magnification and recorded as the percentage of c-erbB-2 and bcl-2 positive tumor cells over the total number of cells examined in the same area. The percentage scores were subsequently categorized using the 5% cut-off point for positive staining. Results: The MN was significantly increased in IBC and in IDPL patients compared to BBL patients (3.82 ± 0.17 and 2.37 ± 0.52, respectively, vs. 1.61 ± 0.40, P < 0.001). On other hand, the MN frequencies in IBC patients were higher than those in IDPL patients (3.82 ± 0.17 vs. 2.37 ± 0.52, P < 0.01). c-erbB-2, had the highest record in IBC (60%), and the score was not observed in both IDPL and BBL: bcl-2 immunostaining was also assessed, the lowest recorded score was in IBC (46.66%) and the highest in both BBL and IDPL (100%). Furthermore, there was a significantly difference in the mean MN frequency between c-erbB-2 positive IBC patients (4.06 ± 0.48) and c-erbB-2 negative IBC patients (3.44 ± 0.39) (P < 0.05). Conclusions: Our results suggest that increased chromosome / DNA instabilities may be associated with the pathogenesis of early BC.